Transcranial magnetic stimulation studies in complex regional pain syndrome type I: A review. (3rd October 2017) - Nardone, R.; Brigo, F.; Höller, Y.; Sebastianelli, L.; Versace, V.; Saltuari, L.; Lochner, P.; Trinka, E.
Abstract : The sensory and motor cortical representation corresponding to the affected limb is altered in patients with complex regional pain syndrome (CRPS). Transcranial magnetic stimulation (TMS) represents a useful non‐invasive approach for studying cortical physiology. If delivered repetitively, TMS can also modulate cortical excitability and induce long‐lasting neuroplastic changes. In this review, we performed a systematic search of all studies using TMS to explore cortical excitability/plasticity and repetitive TMS (rTMS) for the treatment of CRPS. Literature searches were conducted using PubMed and EMBASE. We identified 8 articles matching the inclusion criteria. One hundred fourteen patients (76 females and 38 males) were included in these studies. Most of them have applied TMS in order to physiologically characterize CRPS type I. Changes in motor cortex excitability and brain mapping have been reported in CRPS‐I patients. Sensory and motor hyperexcitability are in the most studies bilateral and likely involve corresponding regions within the central nervous system rather than the entire hemisphere. Conversely, sensorimotor integration and plasticity were found to be normal in CRPS‐I. TMS examinations also revealed that the nature of motor dysfunction in CRPS‐I patients differs from that observed in patients with functional movement disorders, limb immobilization, or idiopathic dystonia. TMS studies may thus lead to the implementation of correct rehabilitation strategies in CRPS‐I patients. Two studies have begun to therapeutically use rTMS. This non‐invasive brain stimulation technique could have therapeutic utility in CRPS, but further well‐designed studies are needed to corroborate initial findings.